Short report: factors determining perceived stress among medical staff in radiology departments during the COVID-19 outbreak. Issue 1 (2nd January 2021) - Huang, Lei; Wang, Yun; Liu, Juan; Ye, Pengfei; Chen, Xijian; Xu, Huayan; Guo, Yingkun; Qu, Haibo; Ning, Gang
ABSTRACT: Medical staff in radiology departments faces a higher risk of infection and a heavier workload during the new coronavirus disease (COVID-19) outbreak. High perceived stress levels endanger physical and mental health and affect work efficiency and patient safety. Therefore, it is urgent to understand the perceived stress levels of medical staff and explore its risk factors. We recruited 600 medical staff from the radiology departments of 32 public hospitals in Sichuan Province, China, to evaluate perceived stress scores via a mobile app-based questionnaire. The results showed that the perceived stress level among medical staff in the radiology departments during the COVID-19 outbreak was high and a sense of tension was strongly present. A positive correlation was found between anxiety score and perceived stress. Multivariate analysis showed that risk factors for perceived stress were female, existing anxiety, and fears of being infected at work, an uncontrollable outbreak, and not being able to pay rent or mortgage. Conversely, good knowledge about COVID-19, being unmarried, and working in a higher-grade hospital were protective factors for perceived stress. Therefore, more attention should be given to medical staff in the radiology departments that present the risk factors outlined above. Timely risk assessment of psychological stress and effective intervention measures should be taken for these high-risk groups to keep their perceived stress within normal limits.